Impostor Syndrome as Viewed Through the Lens of Self-Efficacy and Social Comparison Among University Graduates in Indonesia - Yuliyanti Setivani; Rr Dwi Astuti (Varied Knowledge Journal, 2026)
This study examined the relationship between self-efficacy and social comparison with impostor syndrome among Indonesian fresh graduates. Impostor syndrome has become increasingly prevalent during the transition from higher education to the workforce, as graduates often experience self-doubt, fear of being perceived as incompetent, and difficulty recognizing their achievements. A quantitative correlational design was employed involving 305 Indonesian fresh graduates who had graduated within the previous two years and were selected through purposive sampling. Data were collected using scales measuring impostor syndrome, self-efficacy, and social comparison. The data were analyzed using multiple regression analysis and Pearson product-moment correlation. The findings indicated a significant simultaneous relationship between self-efficacy and social comparison with impostor syndrome (R = 0.660; R² = 0.435; p < 0.001). Self-efficacy was negatively associated with impostor syndrome, whereas social comparison was positively associated with impostor syndrome. The results suggested that individuals with higher self-efficacy tended to experience lower levels of impostor syndrome, while those who engaged more frequently in social comparison tended to experience higher levels of impostor syndrome. These findings highlighted the importance of strengthening self-efficacy and managing social comparison during the transition from university to professional life.